The London Art of Plagiarisn, Part One - Lucraft, Fiona (Petits Propos Culinaires, 1992)
In 1783 a book called The London Art of Cookery and Housekeeper’s Complete Assistant was published, as the work of ’John Farley, Principal Cook at the London Tavern’. It was a popular success and had reached its 12th edition by 1811. In 1989 the author of this essay, an enthusiastic amateur cook with literary and historical interests, borrowed simultaneously from a library a reprint of Farley’s book and a reprint of Elizabeth Raffald’s The Experienced English Housekeeper. As a result, one of the boldest and biggest and most cunning acts of plagiarism in the whole history of cookery books has, after 200 years of successful deception, been exposed. We particularly asked Fiona Lucraft to describe her detective work in detail, not only because of its intrinsic fascination but also because the details throw interesting light on a host of subsidiary matters.